CD8+ T-Cells Count in Acute Myocardial Infarction in HIV Disease in a Predominantly Male Cohort. (19th January 2015) - Badejo, Oluwatosin A.; Chang, Chung-Chou; So-Armah, Kaku A.; Tracy, Russell P.; Baker, Jason V.; Rimland, David; Butt, Adeel A.; Gordon, Adam J.; Rinaldo, Charles R.; Kraemer, Kevin; Samet, Jeffrey H.; Tindle, Hilary A.; et al.
Abstract : Human Immunodeficiency Virus- (HIV-) infected persons have a higher risk for acute myocardial infarction (AMI) than HIV-uninfected persons. Earlier studies suggest that HIV viral load, CD4 + T-cell count, and antiretroviral therapy are associated with cardiovascular disease (CVD) risk. Whether CD8 + T-cell count is associated with CVD risk is not clear. We investigated the association between CD8 + T-cell count and incident AMI in a cohort of 73, 398 people (of which 97.3% were men) enrolled in the U.S. Veterans Aging Cohort Study-Virtual Cohort (VACS-VC). Compared to uninfected people, HIV-infected people with high baseline CD8 + T-cell counts (>1065 cells/mm 3 ) had increased AMI risk (adjusted HR = 1.82,   P < 0.001, 95% CI: 1.46 to 2.28). There was evidence that the effect of CD8 + T-cell tertiles on AMI risk differed by CD4 + T-cell level: compared to uninfected people, HIV-infected people with CD4 + T-cell counts ≥200 cells/mm 3 had increased AMI risk with high CD8 + T-cell count, while those with CD4 + T-cell counts <200 cells/mm 3 had increased AMI risk with low CD8 + T-cell count. CD8 + T-cell counts may add additional AMI risk stratification information beyond that provided by CD4 + T-cell counts alone.